A FOUR-NODE 3D ISOPARAMETRIC MEMBRANE ELEMENT - ANDRZEJ AMBROZIAK; PAWEŁ KŁOSOWSKI (TASK Quarterly, 2006)
The paper presents a non-linear finite element procedure for analysis of membrane structures. A four-node quadrilateral finite element is formulated to represent a general curved elastic geometrically non-linear surface. The described isoparametric element is C0 -continuous, of constant thickness, and assumes a plane stress criterion. A simple numerical example is presented as an application of the described theory.